Critical Discourse Analysis (CDA) towards Early Marriage Women’s Causality in East Lombok - Nahdi, Khirjan (International Journal of Psychosocial Rehabilitation, 2020)
Early marriage is always attributed to low education, skills, and income, as well as poverty. However, this is a problem that leads to the violation of women’s basic rights and needs attention from relevant authorities. Some women enter into early marriages due to the unrealistic expectation that their welfare might improve. This study aims to determine the causes of early marriage with various strategic aspects in East Lombok, including ethnographic surveys, in-depth interviews, and analysis of CDA. The research found that early marriage is perceived as a normal phenomenon in society. This makes the society a structure that perpetuates various forms of discrimination with adverse consequences for women in gender relations.